Creativity And Responsibility As A Manifestation Of Freedom On Person’s And Mankind’s Level In The Eastern Ontology - Лимар, В. Б. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. Ontology as a complex of the results of Antique and Eastern sights, confirms that the being is the point of existence that’s why it spreads its competence on integrity of transcendental and immanent. The research includes theology, anthropology and psychology as well and the later scientific achievements in the spare of studying the human’s being – consciousness, developing of inner and outer, genetics, bioethics and in some point the exact sciences of universe’s design and human body. Despite the metaphysics criticism of M. Haideher’s “The Being and the Time”, modern representatives of the Eastern orthodox like H. Yannaras’s “The Personality and the Eros” and Ioann Ziziulas’s “Communion and Otherness” delight the ability of this ontology in clearly researching of being and existence as these display. The aim and tasks. Considering the backgrounds above, the main purpose of the dissertation is the researching of human’s manifestation as a creativity and responsibility on ontological degree of the person separately and the humanity in general. Applying the “traditionalism’s” access of the Eastern ontology, the main task is to delight the borders of freedom on personal level that indirectly or straight influences history and everyday developing of all the humanity in general. Research methods. The methodology of the study is an extensive analysis of the provisions of "traditionalism" and the inductive application of the results obtained in relation to the personality and totality of the peoples that generally form humanity. Research results. The research gradually shows the principle The Creator doesn’t interfere the humans’ freedom and follows “the sacralization” of the ones, enables the full detection of the creation, (if it doesn’t conflict with the universe’s design), but also being the result of positive and negative creativity. Separate points should be taken that precede the person’s birth. This one, including national, cultural and natural factors mainly influences developing freedom’s displays. Discussion. A newborn child derives some ontological level from his parents, which specifies the rate of child’s further ontological development. At the same time a man is able to achieve the given level (realize himself) and, moreover, with the help of synergism of divine powers, to leave it behind. The very amplitude of ontological development is clearly defined by pairs of ontological modalities “necessity – accidential”, “reality – possibility”. Conclusion. As a result, the personal’s being degree confirms the overpass from ontological level of separate peoples to its internal manifestation – religion, and its outer cultural – the one as it has been understood.